A Clinicopathological Report of a 93-Year-Old Former Street Boxer With Coexistence of Chronic Traumatic Encephalopathy, Alzheimer's Disease, Dementia With Lewy Bodies, and Hippocampal Sclerosis With TDP-43 Pathology - Yang, Chunhui; Nag, Sukriti; Xing, Guoqiang; Aggarwal, Neelum T.; Schneider, Julie A. (Frontiers in Neurology, 2020)
Chronic traumatic encephalopathy (CTE) was recently recognized as a new tauopathy in which multifocal perivascular phosphorylated tau aggregates accumulate in neurons, astrocytes, and neurites at the depths of the cortical sulci. Traumatic brain injury (TBI) in early or mid-life is known to be associated with an increased risk of dementia in late life. This case report describes a 93-year-old former street boxer with a premortem diagnosis of severe dementia, who showed pathological evidence of the coexistence of Alzheimer's disease, CTE, dementia with Lewy bodies, and hippocampal sclerosis with TDP-43 pathology. These findings suggest that TBI may trigger a variety of misfolded proteins leading to dementia. Currently, clear clinical diagnostic criteria for CTE have not been established. Therefore, clinicians should be aware that TBI is a risk factor for dementia and that CTE can overlap with other neurodegenerative diseases.